Experimental and thermodynamic analysis of a bottoming Organic Rankine Cycle (ORC) of gasoline engine using swash-plate expander. (October 2015) - Galindo, J.; Ruiz, S.; Dolz, V.; Royo-Pascual, L.; Haller, R.; Nicolas, B.; Glavatskaya, Y.
Highlights: An experimental analysis of an ORC is presented and applied to a gasoline engine. 28 Steady-state operating points have been tested to evaluate expander performance. Optimum points have been used to analyze power balances and cycle efficiencies. Abstract: This paper deals with the experimental testing of an Organic Rankine Cycle (ORC) integrate in a 2 liter turbocharged gasoline engine using ethanol as working fluid. The main components of the cycle are a boiler, a condenser, a pump and a swash-plate expander. Five engine operating points have been tested, they correspond to a nominal heat input into the boiler of 5, 12, 20, 25 and 30 kW. With the available bill of material based on prototypes, power balances and cycles efficiencies were estimated, obtaining a maximum improvement in the ICE mechanical power and an expander shaft power of 3.7% and 1.83 kW respectively. A total of 28 steady-state operating points were measured to evaluate performance of the swash-plate expander prototype. Operating parameters of the expander, such as expander speed and expansion ratio, were shifted. The objective of the tests is to master the system and understand physical parameters influence. The importance of each parameter was analyzed by fixing all the parameters, changing each time one specific value. In these sensitivity studies, maximum ideal and real Rankine efficiency value of 19% and 6% were obtained respectively.